Preventing Radiolytic Degradation by Addition of Various Inhibitors/Scavengers - Marcus, Hedberg (My University, 2011)
Radiolysis during solvent extraction in reprocessing of used nuclear fuel is a problem. One potential solution to this problem may be the addition of an inhibitor/scavenger. Due to the ionizing radiation emanating from the used nuclear fuel several reactive compounds are formed during reprocessing, such as solvated electrons and various kinds of radicals. Such reactive species degrade the molecules used for extracting the desired material from the used nuclear fuel. The purpose of a scavenger would be to react with these electrons and radicals, and thereby protect the extracting agents used. Work was performed using two different extracting ligands: TBP (TriButyl Phosphate) and C2-BTBP (6,6’-Bis-(5,6-diethyl-[1,2,4]-Triazine-3-yl)-2,2’-BiPyridine). TBP is an extracting agent used for recovery of uranium and plutonium from used fuel. C2-BTBP and the BTBP class as general are designed to separate minor actinides such as americium and curium. BTBPs are not used in industrial applications today, but are rather being investigated at a research level. Irradiation of solutions containing either TBP or C2-BTBP in a cyclohexanone/water system was performed to find a good model system. TBP was determined to be unsuitable for scavenger experiments due to measurement problems. C2-BTBP could be used to examine scavenger effects, since its degradation during irradiation could be measured by the solvent extraction technique used. Several different substances was tested as scavengers and it was observed that nitrobenzene, 2,4-dihydroxyacetophenone and 2,6-di-tert-butyl-4-methylphenol all to various degree can be utilized as radiolysis inhibitors. During the experiments, indications that the protective features of some scavengers might be attributed to an ability to scavenge formed radicals in the sample rather than solvated electrons were observed.
Keywords: Kemi; Chemical Sciences